2018
DOI: 10.1111/head.13405
|View full text |Cite
|
Sign up to set email alerts
|

Survey Analysis of the Use, Effectiveness, and Patient‐Reported Tolerability of Inhaled Oxygen Compared With Injectable Sumatriptan for the Acute Treatment of Cluster Headache

Abstract: Therapeutic response to inhaled oxygen at sufficiently high flow rates (>10 L/min) had comparable efficacy to that of injectable sumatriptan for the acute treatment of cluster headache. Other factors in oxygen delivery (ie, flow rate changes) should be explored for optimization of therapy. The reasons for improved oxygen response in males and those with a cigarette smoking history require further exploration. While both oxygen and sumatriptan can be effective in the management of cluster headache, patient-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
0
22
3
Order By: Relevance
“…Oxygen responsiveness has been positively associated with shorter attacks and a lack of interictal pain, and negatively associated with photophobia or phonophobia during an attack, nausea and vomiting during an attack, or restlessness . Previous studies have found conflicting results for associations with age, sex, and history of smoking . Our findings show no association of responses to any acute therapies with any cranial autonomic features examined (rhinorrhea was not examined) and no association with restlessness, photophobia/phonophobia, nausea/vomiting, age (current age or age of onset of cluster headaches), sex, or any other feature examined.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Oxygen responsiveness has been positively associated with shorter attacks and a lack of interictal pain, and negatively associated with photophobia or phonophobia during an attack, nausea and vomiting during an attack, or restlessness . Previous studies have found conflicting results for associations with age, sex, and history of smoking . Our findings show no association of responses to any acute therapies with any cranial autonomic features examined (rhinorrhea was not examined) and no association with restlessness, photophobia/phonophobia, nausea/vomiting, age (current age or age of onset of cluster headaches), sex, or any other feature examined.…”
Section: Discussioncontrasting
confidence: 67%
“…While oxygen is highly effective, it may not be the most effective treatment because all triptans were grouped together. Subcutaneous sumatriptan may be more effective than oxygen based on some previous questionnaires, though a questionnaire that specifically compared oxygen >10 L/min to injectable sumatriptan found no difference in effectiveness . Thus higher doses of oxygen at 10‐15 L/min or more, which are used in clinical practice, may be the most effective doses of oxygen.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effectiveness of high-flow oxygen in CH is remarkable; it is well tolerated with few adverse events; it is applicable repeatedly throughout the day and can also be combined with other treatments [16,19,20]. The major drawback for oxygen use is the portability of the cylinders [21].…”
Section: Oxygenmentioning
confidence: 99%
“…Clusterbusters sought to examine some of these topics in their Medication Use Survey, which was a large online survey executed in 2012 and published previously by authors EADS, DAW, and MJW. 2,5 In the current report, we analyzed the free-text comments provided by survey participants and used qualitative and quantitative techniques to identify themes that were not queried within the structured survey questions. The hypothesis of this exploratory project was that topics about cluster headache that are not widely known would be identified.…”
Section: Introductionmentioning
confidence: 99%